Freedom to choose religious affiliation from the perspective of religions in Malaysia - Halim, Rohizan; Ahmad, Rusniah; Abdul Rahman, Rohana; Romli, Fariza (Global Academic Excellence, 2018)
Malaysia is a country of many races, nations and religions. The Malaysian Constitution provides for freedom of profession and practice of religion for all citizens under Article 11(1) of the Federal Constitution. However, there is little difference in terms of the freedom to choose the religion where for Muslims, they cannot freely change religion. If they want to go out of Islam, they have to follow the established procedures. The confusion arises in terms of existing legislation where not all states provide clear procedures for renouncing Islam while punishment on the basis of insulting Islam awaits those who renounce Islam in other states where there is no clear provision. From a religious point of view, there is a difference in terms of acceptance to go out or enter the religion. This paper examines the right in aspect of converting to another religion from the perspective of four religions that have many believers in Malaysia namely Islam, Christianity, Buddhism and Hinduism. The findings show that choosing another religion is a major sin in the teachings of Islam. For Christianity, choosing another religion is a sin that will be punished in the Day of Judgment while for Hinduism and Buddhism there is no barrier to choose other religions.